ANALYSIS OF STUDY PERMIT POLICY FOR CIVIL SERVANTS IN THE MANDAILING NATAL REGENCY GOVERNMENT - Ahmad, Kirsa; Ritonga, Syafruddin; Lubis, Maksum Syahri (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study analyzes the study permit policy for Civil Servants (PNS) in Mandailing Natal Regency as part of efforts to improve the quality of human resources in the government sector. The purpose of this study is to understand the impact of the study permit policy on the competence, performance, and motivation of civil servants and to identify obstacles in its implementation. The research method used is qualitative descriptive with interview techniques and document analysis. The results of the study show that study permits have a positive impact on improving the technical competence and work motivation of civil servants, which contributes to a better quality of public services. However, the implementation of this policy faces obstacles, especially in terms of complex administrative procedures and limited regional budgets, which limit the number of civil servants who can participate in this program. Based on these findings, it is recommended that local governments simplify administrative procedures and increase budget allocations for study permits so that they can be accessed by more civil servants. Thus, this policy can function as an effective human resource development instrument, support bureaucratic reform, and improve the quality of public services in Mandailing Natal Regency.